Grafting of Poly (Cysteine Methacrylate) Brush from Polysulfone Membrane via Surface-Initiated ATRP and Their Anti-Protein Fouling Property (Journal of Fiber Bioengineering and Informatics, 2018)
In this paper, we first grafted the poly cysteine methacrylate (pCysMA) brush on polysulfone membrane by surface-initiated atomic-transfer radical polymerization and studied for their antifouling properties. The surface topological structure, chemical composition, and wettability of the as-prepared surface are characterized by scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM), fourier transform infrared spectra (ATR-FTIR), and water contact angle (WCA) measurements. The hydrophilicity and anti-biofouling activities of the polymer brush surface were evaluated by protein adsorption test. The results displayed that the pCysMA shows better hydrophilicity and effectively resisted the adsorption of bovine serum albumin (BSA) protein.